Public Spending and Growth in an Economic and Monetary Union : The Case of West Africa - Moreno-Dodson, Blanca (World Bank, Washington, DC, 2015)
The focus of the paper is on how public spending volume, composition (current versus capital), and quality are linked to the per capita growth rates of the West Africa economic and monetary union (WAEMU) countries, which have been fluctuating and remain relatively low compared to other parts of the world. The empirical analysis covers the period 2000-2013. The results indicate that total public spending has a significant impact on growth. While the impact of the capital component is positive and statistically significant, the effect of the current component is consistently negative, but not significant. When the capital component is further split into two: public fixed capital investment and public other capital expenditures, defined as total public capital expenditure minus public fixed capital investment, the results show that not only physical capital formation but also human capital spending is important for growth in the WAEMU group. While the volatility measure for public investment has a clear negative and statistically significant impact on growth, the quality of public fixed investment has a positive impact. The findings also indicate that fiscal deficits have not been an important constraint to the effectiveness of government spending on growth, reflecting the fiscal discipline achieved in the union. On the other hand, the debt-to-gross domestic product (GDP) ratio clearly shows a significant negative impact on growth, indicating the risk associated with debt distress. Total fiscal revenue has a significant and positive effect on growth, most likely indicating relatively low levels of fiscal revenues to GDP ratios, partially boosted by natural resources, coupled with grants. In each regression specification, it is observed that the contributions of both trade openness and private investment on growth are positive and significant. The results also indicate that the quality of institutions, measured by an index of bureaucracy quality, is critical to enhancing the positive effect of public spending on growth. The results with country effects indicate that, at the individual country level, capital public expenditures are clearly much more relevant in explaining growth changes than current expenditures. The findings are robust to different regression methodologies, as well as the inclusion of short- and medium-term data.